Credit CARD Act of 2009: What did banks do? - Jambulapati, Vikram; Stavins, Joanna (Journal of Banking & Finance, 2014)
The Credit CARD Act of 2009 was intended to prevent practices in the credit card industry that lawmakers viewed as deceptive and abusive. Among other changes, the Act restricted issuers’ account closure policies, eliminated certain fees, and made it more difficult for issuers to change terms on credit card plans. Critics of the Act argued that because of the long lag between approval and implementation of the law, issuing banks would be able to take preemptive actions that might disadvantage cardholders before the law could take effect. Using credit bureau data as well as individual data from a survey of U.S. consumers, we test whether banks closed consumers’ credit card accounts or otherwise restricted access to credit just before the enactment of the CARD Act. Because the period prior to the enactment of the CARD Act coincided with the financial crisis and recession, causality in this case is particularly difficult to establish. We find evidence that a higher fraction of credit card accounts were closed following the Federal Reserve Board’s adoption of its credit card rules, but not between May 2009, when the CARD Act was signed, and when most of its provisions became law in February 2010. However, we do find evidence that banks deteriorated terms of credit card plans at a higher rate during this period, especially lowered the credit limits. Among the survey respondents whose bank accounts were closed during that period, account holders were much more likely to close their own credit card accounts than to have them closed by their card issuers.